Contribution of Emotional, and Physical Support of Fathers in Exclusive Breastfeeding - Nasution, Ade Saputra; Putri, Devia Lydia; Nuraida, Ida; Rahayu, Yayuk Sri; Handayani, Ida Farida; Yanuaringsih, Galuh Pradian (Al-Sihah: The Public Health Science Journal, 2024)
Exclusive breastfeeding coverage in Bogor Regency remains low, affecting infant growth and development during the first six months of life. Paternal support, as a key determinant, has been insufficiently explored. This study assessed the types of support fathers provide to breastfeeding mothers. Exclusive breastfeeding is a critical effort to support the optimal growth and development of infants during the first 6 months of life. Nevertheless, exclusive breastfeeding coverage continues to be insufficient in certain regions, including Bogor Regency. This study aimed to analyze the relationship between paternal support and the success of exclusive breastfeeding. The study employed a quantitative design with a cross-sectional approach, involving 221 parent pairs selected through purposive sampling. Data were collected using a structured questionnaire that assessed various forms of paternal support, including physical, emotional, and educational assistance. The data were analyzed using chi-square tests to determine the statistical associations. The results revealed that instrumental support—such as helping to change diapers and holding the baby—was not significantly associated with exclusive breastfeeding practices (p > 0.05). Conversely, paternal support in the form of accompanying mothers during consultations with health workers demonstrated a significant association with exclusive breastfeeding success (p = 0.023 < 0.05) This study confirms the critical role of educative and emotional support from fathers in promoting exclusive breastfeeding success. The findings highlight the strategic role of fathers in promoting exclusive breastfeeding and support the development of family-based interventions to increase its coverage.